Examining the challenges of the COVID-19 pandemic for regional integration in Africa - Atta, Francis Kwabena (Research Journal in Advanced Humanities, 2020)
The covid-19 pandemic has had effect on all facets of human life. Regional integration is no exception. Meanwhile, regional integration has been largely held as one of the most feasible avenues for developing countries to achieve prosperity. This paper examines why African states took decisions that were in violation of regional integration protocols when faced with the covid-19 scourge. Four policy briefs about the effects of the covid-19 pandemic on regional integration in Africa were analysed using the qualitative content analysis method. The findings were interpreted through the lens of a rationalist actor choice model. The study found that state actors in Africa took decisions that broke regional integration protocols. These decisions were the result of severe limitations imposed by the pandemic against the desire of actors to maximise interests. The findings contradict a popular view expressed by the authors of the policy briefs who appeared to portray deliberate actions on the part of state actors to impose border closures and trade restrictions. The pandemic has unveiled a reality in the risk of overrating how far states can go in their search for integration. States as rational actors will always choose survival over loyalty. State actors would need to exercise more caution in their commitment to regional integration regimes.